Perancangan Standar Prosedur Operasional Pelepasan Informasi Rekam Medis di RSU Gotong Royong Surabaya - Masyfufah, Lilis; Pangestu, Raden Bagus Mochammad Tahta; Saadah, Alfina Aisatus; Erica, Resty Nadia Bella (Lembaga Penerbitan Universitas Esa Unggul, 2025)
AbstractThe development of Standard Operating Procedures (SOP) for each staff activity is essential to ensure patient safety, improve service quality, and prevent malpractice claims. SOPs serve as control tools for both clinical and administrative services provided to patients. Gotong Royong General Hospital has not yet established an SOP for the release of medical information, resulting in unstandardized procedures, particularly regarding processing time and fees charged to patients. This study aimed to design an SOP for the release of medical information at the hospital. A descriptive qualitative approach was applied, using questionnaires for data collection, followed by confirmation with the respondents. The study was conducted in the Medical Records Unit of Gotong Royong General Hospital during April–May 2024. The object of this study was the SOP draft, while the subjects were medical records staff involved in releasing patient information. Data obtained from the questionnaires were analyzed and presented narratively. The results showed that the proposed SOP included time limits for processing requests, official payment through receipts recorded in the hospital information system, the use of a stamped authorization letter, and a clear flow of information release for patients. The hospital is advised to consider implementing the SOP, as it has been adjusted to suit the operational context. Socialization efforts are also needed to inform patients through official media such as banners.Keywords: SOP, medical information, medical records, service quality, socialization AbstrakPenyusunan Standar Prosedur Operasional (SPO) bagi setiap tindakan petugas merupakan langkah penting dalam menjaga keselamatan pasien, meningkatkan mutu pelayanan, serta menghindari risiko malpraktik. SPO berfungsi sebagai alat kendali terhadap layanan yang diberikan, baik layanan kesehatan maupun administrasi. Rumah Sakit Umum Gotong Royong belum memiliki SPO pelepasan informasi medis, sehingga pelaksanaannya belum terstandar, khususnya terkait waktu penyelesaian dan biaya yang dibebankan kepada pasien. Penelitian ini bertujuan untuk merancang SPO pelepasan informasi medis di rumah sakit tersebut. Penelitian menggunakan pendekatan deskriptif kualitatif, dengan pengumpulan data melalui penyebaran kuesioner dan proses konfirmasi hasil kepada responden. Penelitian dilakukan di Unit Rekam Medis Rumah Sakit Umum Gotong Royong pada April–Mei 2024. Objek penelitian adalah rancangan SPO, sedangkan subjeknya adalah petugas rekam medis yang terlibat dalam pelepasan informasi medis pasien. Data hasil kuesioner dikaji dan disajikan dalam bentuk narasi. Hasil penelitian menunjukkan bahwa rancangan SPO yang disusun telah mencakup batasan waktu proses pelepasan informasi, sistem pembayaran resmi melalui nota tercatat di SIMRS, penggunaan surat kuasa bermaterai, serta alur pelepasan informasi yang jelas bagi pasien. Rumah Sakit Umum Gotong Royong disarankan untuk mempertimbangkan implementasi SPO tersebut, karena telah disesuaikan dengan kondisi di lapangan. SPO ini juga perlu disosialisasikan kepada pasien melalui media resmi seperti banner.Kata kunci: SPO, informasi medis, rekam medis, pelayanan, sosialisasi